Rate of Nondiagnostic Computerized Tomography Pulmonary Angiograms (CTPAs) Performed for the Diagnosis of Pulmonary Embolism in Pregnant and Immediately Postpartum Patients - Sarah Hogan; Jillian Greene; Jeffery Flemming (Hindawi Limited, 2019)
Objective. To evaluate the nondiagnostic rate of computed tomography pulmonary angiography (CTPA) in pregnant and postpartum patients with suspected pulmonary embolism (PE) to determine whether CTPA or ventilation-perfusion (VQ) scan should be considered first line imaging in this patient population considering their equivalent accuracy and the greater radiation exposure to proliferating breast tissue of CTPA. Methods. All pregnant/postpartum female patients between 18 and 50 years of age who had CTPA within the Eastern Health Authority between November 2012 and November 2016 were included. Each scan was evaluated for nondiagnosis based on two criteria: contrast density in the main pulmonary artery, and respiratory motion artefact. If either of these criteria were not met, the scan was labelled as nondiagnostic. Results. The nondiagnostic rate overall was 43% (n=83). This is similar to current literature values for rates of CTPA nondiagnosis, and comparable to the reported diagnostic quality of the reporting radiologist. This is much greater compared to rates of ventilation/perfusion nondiagnosis in comparable populations. Even in patients with normal chest radiographs, which represents the main patient group where VQ may be considered as an alternative, the nondiagnostic rate of CT is much higher. Conclusion. This is the first study to attempt to identify an objective method of determining nondiagnosis in pregnant and postpartum patients undergoing a CTPA. Our results strengthen the argument that alternative imaging should be considered when investigating for PE in this population in order to protect the proliferating breast tissue, and VQ scan should be considered especially in patients with normal chest X-rays.